EFFECT OF SAMBILOTO (Andrographis paniculata Ness.) EXTRACT ON IMPLANTATION AND RATIO OF FEMALE MALE MICE (Mus musculus L.) - zumiro tiljannah (Serambi Biologi, 2018)
Background this study was to examine the influence of extract of bitter against implantation and ratio of male female in mice. The purpose of this research is to know the influence of extract of bitter (Andrographis paniculata Ness.) against implantation and ratio male female mice (Mus musculus L.).This type of research is research experiments using Completely Randomized Design (CRD), which consists of 4 treatments and 6 replicates. This research procedure is the preparation of the implementation phase, research and observations. Data were analyzed with ANOVA (analysis of Variance) and if the results of the data analysis shows the influence of then continued with test List Significant Different (LSD) on p<0.05.The results showed that the sambiloto extract could reduce the number of implants, the number of birth fetuses, and the ratio of female tillers but did not cause a decrease in the number of corpus luteum, body weight, and ratio of male mice (Mus musculus L.). the ratio of male and female tillers is different because the female fetus has a weaker survival compared to the male, so the sambiloto content causes a decrease in the number of female tiller ratio.